Răspuns :
[tex] | \frac{x}{2} - \frac{3}{4} | = \frac{1}{2} \\ \\ \frac{x}{2} - \frac{3}{4} = \frac{1}{2} \\ \\ - ( \frac{x}{2} - \frac{3}{4}) = \frac{1}{2} \\ \\ \frac{x}{2} = \frac{1}{2} + \frac{3}{4} = \frac{5}{4} \\ \\ x = \frac{5}{4} \times 2 = \frac{10}{4} \\ \\ x = \frac{5}{2} \\ \\ - \frac{x}{2} + \frac{3}{4} = \frac{1}{2} \\ \\ \frac{3}{4} - \frac{x}{2} = \frac{1}{2} \\ \\ - \frac{x}{2} = \frac{1}{2} - \frac{3}{4} = - \frac{1}{4} \\ \\ - x = - \frac{1}{4} \times 2 = - \frac{2}{4} \\ \\ x = - \frac{1}{2} \\ \\ x = \frac{1}{2} [/tex]